L2 Proficiency Pairing, Task Type and L1 Use: A Mixed-Methods Study on Optimal Pairing in Dyadic Task-Based Peer Interaction - Tian, Lili; Jiang, Yan (Frontiers in Psychology, 2021)
While task-based peer interaction in dyads has been commonly practiced in English as a foreign language (EFL) classrooms, how to pair learners in dyadic tasks has always been a concern of teachers and researchers. This study examined learner proficiency pairing, task type and L1 use by Chinese EFL learners in two dyadic speaking tasks. Thirty-six participants were paired according to their oral English proficiency levels into: same-level pairs (high-high; medium-medium; low-low), and mixed-level pairs (high-low). All pairs completed two types of speaking tasks – information-gap and opinion-exchange tasks. Quantitative results showed a significant difference between low-low pairs and other pairs in the amount of L1 use. Low-level learners produced significantly more L1 words and turns when paired with other low-level peers (low-low) than with high-level peers (high-low) in both types of tasks. Qualitative analysis further indicated that the mixed-level (high-low) pairs produced more opportunities for negotiation of meaning than the same-level (low-low) pairs during the interactional episodes where the L1 served various functions. The study offers pedagogical implications for EFL teachers about how to optimally pair learners to maximize their language development.